The Customer Satisfaction, A Continuing Priority in Economics - Alexandru Trifu (Association of Social and Educational Innovation, 2017)
The problem of the customers' satisfaction is very usual in Economics literature, mainly in the Marketing field of analysis. In this paper we used a very common marketing tool: the questionnaire, in order to see and to conclude about the satisfaction of the clients of a tourism location, such as a hotel. We also try to introduce some Philosophical aspects, especially from Immanuel Kant's ideas, regarding the knowledge and the possibilities of understanding the reality, passed through the mind's filter, adding customers' perceptions, a priori beliefs and other subjective traits. On the other hand, the use of the questionnaire is very sensitive, also from the Philosophical point of view, because we don't know exactly how accurate are the answers, or if we questioned a significant sample of customers. At sum, including economic and philosophic aspects, the satisfaction of customers is obviously illustrated in the study.